Misinformation in social media: The role of verification incentives - Gonzalo Cisternas; Jorge Vásquez (Federal Reserve Bank of New York, 2022)
We develop a model of misinformation wherein users' decisions to verify and share news of unknown truthfulness interact with producers' choices to generate fake content as two sides of a market that balance to deliver an equilibrium prevalence and pass-through of fake news. We leverage the tractability of the model to examine the efficacy of various policies intended to combat misinformation that are in place currently, stressing how these may nontrivially interact with users' incentives: news verification is a costly activity. Our analysis emphasizes the importance of examining users' and producers' decisions jointly, as well as of evaluating how policies interact with one another. It also provides sensitivity measures that are key for policy evaluation.
Keywords: D40; L10; L50; 330; misinformation; news verification; social media